The Antitumor Activity and Mechanism of a Natural Diterpenoid From Casearia graveolens - Li, Ying; Ma, Jun; Song, Ziteng; Zhao, Yinan; Zhang, Han; Li, Yeling; Xu, Jing; Guo, Yuanqiang (Frontiers in Oncology, 2021)
In the process of our continuous effort to discover bioactive natural products, some diterpenoids were isolated and identified from Casearia graveolens and one of them (casearlucin A) was found to have strong cytotoxic activity, which drew our interest in further research. Besides the cellular experiments, the in vivo anti-tumor effects were examined using a zebrafish tumor xenograft. The anti-tumor mechanism was further explored, which revealed casearlucin A arrested cell cycle at G0/G1 stage and induced cell apoptosis in cell level. Additionally, casearlucin A inhibited HepG2 cell migration via regulating a few of metastasis-related proteins. Furthermore, it inhibited tumor angiogenesis in zebrafish in vivo.